2018
DOI: 10.1177/0897190018818907
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Medical Marijuana Claims Made by Popular Websites

Abstract: Background With increasing popularity of marijuana, consumers are likely turning to the internet for information regarding medical marijuana. Accuracy of medical marijuana claims is a significant concern because consumers change their medication management based on information from a single website. Objective The purpose of this study was to evaluate the accuracy and quality of medical marijuana claims on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Similar studies have been conducted in jurisdictions other than Canada, primarily in the United States. In 2014, Boatwright et al evaluated the quality of medical marijuana claims on popular web sites determined by online marketing tools, in which they found that 76% of claims made by web sites were inaccurate and were based on low-quality evidence [ 35 ]. In comparison to the objectives of the present study, Boatwright et al, evaluated the accuracy and quality of only three medical cannabis claims on each web site, as opposed to assessing the entire web site.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have been conducted in jurisdictions other than Canada, primarily in the United States. In 2014, Boatwright et al evaluated the quality of medical marijuana claims on popular web sites determined by online marketing tools, in which they found that 76% of claims made by web sites were inaccurate and were based on low-quality evidence [ 35 ]. In comparison to the objectives of the present study, Boatwright et al, evaluated the accuracy and quality of only three medical cannabis claims on each web site, as opposed to assessing the entire web site.…”
Section: Discussionmentioning
confidence: 99%
“…Few published studies have assessed the quality of online consumer health information specific to cannabis. One study examined the label accuracy of cannabidiol products sold online (Bonn-Miller et al 2017 ), while others have evaluated the accuracy of cannabis claims found on popular websites (Sperry 2018 ), and information specific to cannabis addiction (Khazaal et al 2008 ). Other studies have reviewed the quality of cannabis information published in magazines and newspapers (Halvorson et al 2018 ; MontanĆ© et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…FDA, 2019). Similarly, cannabis retailers are making scientifically unsubstantiated claims about the health benefits of cannabis while simultaneously failing to display appropriate health-related warnings (Berg et al, 2018; Bierut, Krauss, Sowles, & Cavazos-Rehg, 2017; Boatwright & Sperry, 2019; Caputi, 2020; Cavazos-Rehg et al, 2019; Moreno et al, 2018). A related marketing strategy is the use of the word ā€œnaturalā€ for promotion purposes.…”
Section: Cannabis Industry Behaviorsmentioning
confidence: 99%